2016
DOI: 10.1177/2168479016635220
|View full text |Cite
|
Sign up to set email alerts
|

Good Clinical Practice Training: Identifying Key Elements and Strategies for Increasing Training Efficiency

Abstract: Good Clinical Practice (GCP) is an international standard for the design, conduct, performance, monitoring, auditing, recording, analyses, and reporting of clinical trials. The goal of GCP is to ensure the protection of the rights, integrity, and confidentiality of clinical trial participants and to ensure the credibility and accuracy of data and reported results. In the United States, trial sponsors generally require investigators to complete GCP training prior to participating in each clinical trial to foste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…As all of our PI researchers are required to complete the Collaborative IRB Training Initiative program (CITI Program, Miami, FL, citiprogram.org) and to take the refresher course every 3 years, the program developers made a concerted effort to not introduce duplicative information and to instead provide each PI with relevant, actionable information, relevant to the “real world” of research studies [10,11]. The final version of the materials that make up the PINDAR program includes an original 77 slide presentation and presenter study notes, original vignette flash-card exercises, four original mini-cases (relating to the medical care of trial subjects, adequacy of resources, compliance with the protocol, investigational products, records, and reports), two original detailed case scenarios, based on actual events ( Twisting the Vine and The Glass Wall ), portions of the ICH-6 text [6], two published journal articles (assigned as pre-course reading) [12,13], and a relevant publicly available FDA-warning letter [14,15].…”
Section: Pindar Program Developmentmentioning
confidence: 99%
“…As all of our PI researchers are required to complete the Collaborative IRB Training Initiative program (CITI Program, Miami, FL, citiprogram.org) and to take the refresher course every 3 years, the program developers made a concerted effort to not introduce duplicative information and to instead provide each PI with relevant, actionable information, relevant to the “real world” of research studies [10,11]. The final version of the materials that make up the PINDAR program includes an original 77 slide presentation and presenter study notes, original vignette flash-card exercises, four original mini-cases (relating to the medical care of trial subjects, adequacy of resources, compliance with the protocol, investigational products, records, and reports), two original detailed case scenarios, based on actual events ( Twisting the Vine and The Glass Wall ), portions of the ICH-6 text [6], two published journal articles (assigned as pre-course reading) [12,13], and a relevant publicly available FDA-warning letter [14,15].…”
Section: Pindar Program Developmentmentioning
confidence: 99%
“…In fact, the most common deficiencies noted during investigator inspections are directly related to GCP principles [3]. Furthermore, prior studies have identified concerns that clinical research training is redundant [4][5][6], lacking in specificity [7], and unrelated to research validity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns have been raised over the current structure and delivery of GCP training to prepare clinical investigators and their delegates to conduct registrational clinical trials [1,2]. GCP training has been described as timeconsuming [3], emphasizing trial activities unrelated to research validity [4] and providing only the minimum of what is needed in the quality conduct of clinical trials [1]; redundant [1]; lacking specificity about the definition of site quality or clinical investigators' perspectives on site [5]; and having monitoring standards that vary widely across research studies and sites [6,7]. Despite being the industry standard, there is little evidence that completion of GCP training alone sufficiently qualifies investigators and their delegates in the quality conduct of clinical trials [1].…”
Section: Introductionmentioning
confidence: 99%
“…The Clinical Trials Transformation Initiative (CTTI)-a public-private partnership to develop and drive adoption of practices that will increase the quality and efficiency of clinical trials-conducted a two-phased project to gain a broader, evidence-based perspective on the efficient and effective qualification of site investigators and their delegates for the quality conduct of clinical trials. The first phase consisted of a literature review [8], expert interviews, and a survey to assess current GCP training, culminating in recommendations for streamlining GCP training practices [1,9]. These recommendations focused on four components of training: minimum essential elements, training frequency, training format, and evidence of completion [1,9].…”
Section: Introductionmentioning
confidence: 99%